Acting Rightly For The Right Reason: Joseph Raz’s Philosophical Thoughts About Authority - Artha Debora Silalahi (Jurnal Hukum dan Peradilan, 2025)
A philosophical analysis of Joseph Raz’s conception of authority critically examines his claim that the obligation to obey the law is not absolute and is put as the main concern of this article. It highlights the inherent tension between legal rules and moral justification, the raising question of whether a legal system can maintain legitimacy without a convincing ethical foundation. For Raz, authority recognized within a legitimate legal system cannot rely solely on rule-based commands; it must also guide individuals in making morally sound decisions, especially in complex and conflicting circumstances. The article examines how legal systems can building public trust not merely through authoritative resolution, but by reflecting justice-oriented values realized by society., According to Raz, authority achieves legitimacy when it enables individuals to act rightly for the right reasons. Thus, law should not be viewed solely as an instrument of power, but as a moral framework fostering ethical responsibility. The article concludes that legal legitimacy requires the integration of moral values into both legal reasoning and practice, ensuring that authority is not only legally binding but also ethically accountable.